A new genus for two species of Japanese fireflies having aquatic larvae (Coleoptera, Lampyridae) and a definition of Luciola s. str. - Ballantyne, Lesley; Kawashima, Itsuro; Jusoh, Wan F.A.; Suzuki, Hirobumi (European Journal of Taxonomy, 2022)
A new genus Nipponoluciola Ballantyne, Kawashima, Jusoh & Suzuki is proposed and described from males, females and larvae for two species of Japanese fireflies (Coleoptera, Lampyridae, Luciolinae) which have aquatic larvae. The famous Genji-botaru, the Genji firefly, formerly Luciola cruciata Motschulsky, 1854, now stands under Nipponoluciola cruciata (Motschulsky) gen. et. comb. nov. It is proposed that the original designation of this species from Java was in error and that the species is only known from Japan. The lesser known Kumejima-botaru, formerly Luciola owadai Satô & Kimura, 1994, now stands under Nipponoluciola owadai (Satô & Kimura) gen. et comb. nov. A neotype for Luciola cruciata is designated. Keys to adult males and larvae of Luciolinae genera with aquatic larvae are given. An overview of the status of the genus Luciola s. str. is given. Supplementary file addresses 1. Mitogenome analyses of the Luciolinae; 2. List of species of Luciola s. str.; 3. List of Japanese Luciolinae; 4. The identity of Luciola lateralis Motschulsky.